Emotional responses to mortality salience: Behavioral and ERPs evidence. - Shiyun Huang; Hongfei Du; Chen Qu (PLoS ONE)
Terror Management Theory (TMT) suggests that death-related thoughts activate proximal defense which allows people to suppress or rationalize death awareness. So far there is no direct evidence to support the emotional response in the proximal defense process. The current research aimed to address this issue by examining behavioral (e.g., accuracy and reaction time) and neural responses (e.g., P1 and N400 amplitude) related to emotional arousal following death-related thoughts during proximal defense. Before engaged in emotional words (e.g., anxiety, fear and neutral) judgment task, participants answered questions that referred to emotional and physical changes about death to induce mortality salience (MS). In the control condition, participants received similar instructions concerning the experience of watching TV. Behavioral results showed that longer reaction time of words was seen in control group than MS group. The ERPs results showed that after reminders of death-related thoughts, in condition of MS, fear words elicited larger P1 ERP amplitudes, while the control group did not have this effect, which might reflect that emotional words caused different early attention patterns between MS group and control group. Moreover, compared with control group, larger N400 ERP amplitudes were elicited in condition of MS, suggesting larger cognitive inhibition of words processing caused by emotional reaction. The above results indicate that the early stages after mortality salience will induce fear and anxiety, but soon these negative emotions are suppressed and are at a lower level of accessibility. This result provides electrophysiological evidence for the proximal defense hypothesis of terror management theory.